2009
DOI: 10.1016/j.jana.2009.07.004
|View full text |Cite
|
Sign up to set email alerts
|

“I Don't Think This Is Theoretical; This Is Our Lives”: How Erasure Impacts Health Care for Transgender People

Abstract: For people who are transgender, transsexual, or transitioned (trans), access to primary, emergency, and transition-related health care is often problematic. Results from Phase I of the Trans PULSE Project, a community-based research project in Ontario, Canada, are presented. Based on qualitative data from focus groups with 85 trans community members, a theoretical framework describing how erasure functions to impact experiences interacting with the health care system was developed. Two key sites of erasure wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
635
0
44

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 718 publications
(689 citation statements)
references
References 16 publications
10
635
0
44
Order By: Relevance
“…5 Access to health services for trans people is a major issue; long waiting lists exist, funding for treatment is limited, and being trans can present unique dilemmas, for example decisions about which gendered ward patients should stay in. 6 Patients have reported prejudiced, demeaning, incompetent and, in some cases, even abusive treatment from healthcare professionals. Respondents cited these factors as having contributed towards their reasons for self-harm or suicidal thoughts.…”
Section: Wwwtrendsinmenshealthcom Trends In Urology and Men's Health mentioning
confidence: 99%
See 4 more Smart Citations
“…5 Access to health services for trans people is a major issue; long waiting lists exist, funding for treatment is limited, and being trans can present unique dilemmas, for example decisions about which gendered ward patients should stay in. 6 Patients have reported prejudiced, demeaning, incompetent and, in some cases, even abusive treatment from healthcare professionals. Respondents cited these factors as having contributed towards their reasons for self-harm or suicidal thoughts.…”
Section: Wwwtrendsinmenshealthcom Trends In Urology and Men's Health mentioning
confidence: 99%
“…6 This state of affairs, unfortunately, often extends into the healthcare setting (see Box 1 for some examples). A European study surveying trans men and women on their experiences of healthcare found that between 18% and 31% of respondents felt that being trans impacted how healthcare professionals treated them; between 15% and 23% felt that it affected the ways they accessed routine non-trans-related care; and more than 25% reported that they had been refused treatment because a practitioner did not approve of gender reassignment.…”
Section: How Do Health Services Respond?mentioning
confidence: 99%
See 3 more Smart Citations